Risk of arrhythmic death in ischemic heart disease: a prospective, controlled, observer‐blind risk stratification over 10 years. (11th February 2017) - Pezawas, Thomas; Diedrich, André; Robertson, David; Winker, Robert; Richter, Bernhard; Wang, Li; Schmidinger, Herwig
Abstract: Background: Risk of arrhythmic death is considered highest in ischemic heart disease with severe left ventricular ejection fraction (LVEF) reduction. Non‐invasive testing should improve decision‐making of prophylactic defibrillator (ICD) implantation. Design: We enrolled 120 patients with ischemic heart disease and LVEF < 50% and 30 control subjects without ischemic heart disease and normal LVEF. An initial assessment, a second assessment after 3 years and a final follow‐up comprised of pharmacological baroreflex testing (BRS), short‐term spectral [low‐frequency (LF) to high‐frequency (HF) ratio] and long‐term time‐domain analysis of heart rate variability (SDNN), exercise Microvolt T‐wave alternans (MTWA) and others. Results: The median follow‐up was 7·5 years. Resuscitated cardiac arrest and arrhythmic death due to ventricular arrhythmias ≥ 240/min was observed in 18% and 15% of patients, respectively. Cardiac death was observed in 28% of patients. The incidence of arrhythmic death and resuscitated cardiac arrest was identical in patients with ischemic heart disease with LVEF < 30% and ≥ 30%. No significant difference between subgroups with LVEF of < 30%, 30–39% and ≥ 40% was found either. MTWA, BRS, SDNN and LF to HF ratio failed to identify patients at risk of arrhythmic death in a multiple regression model. Conclusions: Ischemic heart disease patients with LVEF < 30% and ≥ 30% face the same risk of arrhythmic death. Stratification techniques fail to identify high‐risk patients. Therefore, the current practice to constrain prophylactic ICDs to patients with severely reduced LVEF seems to be insufficient.